TINGKAT PENGARUH KOMPETENSI, BUDAYA ORGANISASI, DAN KEPEMIMPINAN TERHADAP PENGEMBANGAN KARYAWAN PADA KANTOR CV. GEOPUBLISH INDONESIA MAKASSAR - Amal Amal; Rr Retno Wulansari Kus; Rais Rais; Muhtar Muhtar; Yusri Yusri (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the level of influence of competence, organizational culture, and leadership on employee development at CV. Geopublish Indonesia Makassar. The research method uses a quantitative approach with multiple linear regression analysis techniques. Data were obtained through distributing questionnaires to permanent employee respondents. The results show that competence, organizational culture, and leadership have a positive and significant influence, both partially and simultaneously, on employee development. This finding emphasizes the importance of improving the quality of human resources through the synergy between individual competence, corporate cultural values, and effective leadership styles. Employee development is a company's effort to improve the quality and self-development of its human resources through training, education, and career opportunities. This study employed a quantitative approach with a survey method, collecting data through questionnaires distributed to employees at CV. Geopublish Indonesia. Data analysis was conducted using multiple regression techniques to simultaneously examine the influence of competency, organizational culture, and leadership on employee development. These findings indicate that to improve employee development, CV. Geopublish Indonesia needs to focus on improving competency through appropriate training and building an organizational culture that supports innovation and learning. This study provides recommendations to CV. Geopublish Indonesia's leadership to further optimize development programs that focus on competency and a positive work culture to improve employee quality in the future.